Noninvasive prenatal test for detection of genetic diseases using next-generation sequencing - Silva, Carolina Malcher Amorim de Carvalho (2017)
Since 2011 the prenatal diagnosis field has undergone a revolution with the introduction of a noninvasive prenatal test (NIPT) for genetic diseases relying on analysis of fetal cell-free DNA present in maternal plasma. Although available in Brazil, we rely on outsourcing the technology developed abroad or the test itself. Therefore, our objective was to develop and implement a comprehensive NIPT using high-coverage targeted next-generation sequencing to: 1) estimate fetal fraction; 2) determine fetal sex; 3) detect trisomy; 4) detect monogenic disease. We developed a robust and accurate model (r2= 0.994, p-value < 2.2e-16) for fetal fraction estimation based on distribution of SNP minor allele fraction (MAF). We used Z-score for fetal sex determination (100% accuracy) and trisomy detection of chromosomes 21 (T21) and 18 (T18), achieving a sensitivity of 100% (95% CI: 63.06% - 100.00%) and a specificity of 98.53% (95% CI: 92.08% - 99.96%) for T21, and 40% (95% CI: 5.27% - 85.34%) and 98.59% (95% CI: 92.40% - 99.96%) for T18. For monogenic disease detection (skeletal dysplasia) we performed variant analysis, with 71% (5/7) of detection rate. To our knowledge, this is the first work to integrate all analysis in one single test, and to perform monogenic disease detection without using parental genotype. We showed in this work that it is possible to implement such techniques in our country, using available resources and/or engaging in collaboration with reference research groups abroad. It shows the potential of developing internal technologies, and applying it to other noninvasive fields, such as cancer and organ rejection diagnostic and monitoring